Effective biosynthesis of benzoyl‐pyrrothine dithiolopyrrolone antibiotic by cinnamic acid‐precursor addition in culture of Saccharothrix algeriensis NRRL B‐24137. (1st February 2019) - Merrouche, R.; Yekkour, A.; Coppel, Y.; Bouras, N.; Lamari, L.; Zitouni, A.; Mathieu, F.; Lebrihi, A.; Sabaou, N.
Abstract: Dithiolopyrrolone antibiotics, produced by several micro‐organisms, are known for their strong antimicrobial and antitumor activities. Among of this micro‐organisms, Saccharothrix algeriensis NRRL B‐24137, a rare actinobacterium, has the ability to produce several dithiolopyrrolones derivatives depending on precursors added in the culture medium. After 10 days of strain fermentation on semi‐synthetic medium supplemented with cinnamic acid and HPLC purification, biosynthesis of benzoyl‐pyrrothine dithiolopyrrolone was evidenced through complete spectroscopic (UV–visible and 1H and 13C NMR) and spectrometric (electron impact mass spectrum) analyses. The pure molecule showed appreciable minimum inhibitory concentration values against several Gram‐positive bacteria and filamentous fungi. Significance and Impact of the Study: Dithiolopyrrolone antibiotics, known for their strong antimicrobial activities, gained greater interest after the discovery of their antitumor properties. Depending on precursors added, Saccharothrix algeriensis NRRL B‐24137 has the ability to produce several dithiolopyrrolones derivatives. Since biological activities of dithiolopyrrolones are related to their variable structure, discover of new natural analogues to be therapeutically explored remains a significant framework of research. In this study, a new dithiolopyrrolone derivative was purified from the fermentation broth of S . algeriensis NRRL B‐24137. This new antibiotic, characterized as benzoyl‐pyrrothine dithiolopyrrolone, was induced by adding cinnamic acid, as precursor, to a semi‐synthetic medium.